Effect of Various Factors on the Development of Leaf Spot Disease in Mulberry - Ghosh, L; Neela, FA; Mahal, MF; Khatun, MJ; Ali, MR (Journal of Environmental Science and Natural Resources, 2012)
Effect of various factors such as temperature, relative humidity, balanced fertilizer and plant spacing on the development of leaf spot disease in mulberry caused by Cercospora moricola was studied. High disease development was recorded in the month of August and September when outdoor temperature and relative humidity were 25-30 ºC and above 80%, respectively. Application of balanced fertilizer and plant spacing on this disease development was also studied and showed a distinct effect on severity of this disease. A balanced dose application of NPK fertilizer decreased disease severity to 6-8%. Balanced fertilizer application in the soil resulted lower infection by leaf pathogen in comparison with imbalanced fertilizer application in the soil. Disease development was also found to be high at close plant spacing (60 × 60) cm than distance spacing (90 × 90) cm. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11583 J. Environ. Sci. & Natural Resources, 5(1): 205 - 209, 2012